Fiscal sustainability and policy rules: Under changing demographic forecasts - Jukka Lassila; Tarmo Valkonen; Juha M. Alho (The Research Institute of the Finnish Economy (ETLA), 2011)
All practical evaluations of fiscal sustainability that include the effects of population ageing must utilize demographic forecasts. It is well known that such forecasts are uncertain, and that has been taken into account in some studies by using stochastic population projections jointly with economic models. We develop this approach further by introducing regular demographic forecast revisions that are embedded in stochastic population projections. This allows us to separate systematically, in each demographic outcome and under different policy rules, the expected and the actualized effects of population ageing on public finances. We show that the likelihood of sustainability risks is significant, and that it would be wise to consider policies that reduce the likelihood of getting highly indebted. Furthermore, although demographic forecasts are uncertain, they seem to contain enough information to be useful in forward-looking policy rules.
Keywords: H30; H62; H63; J11; 330; public finance; fiscal sustainability; stochastic population simulations; changing demographic forecasts; Öffentliche Finanzen; Nachhaltigkeit; Alternde Bevölkerung; Bevölkerungsprognose; Overlapping Generations; Finnland